Factors Inducing the Investment and Saving Behaviour in Pakistan - Ashraf, Muhammad Farhan; Latif, Muhammad Mehran; Kanwal, Hina (iRASD Journal of Economics, 2019)
This study endeavour’s to identify in detail the behaviour of investment and saving in Pakistan's economy. Both investment and saving have a dynamic role in economic growth and development. Gross domestic product, remittances, income, dependency rate, taxes, labor participation rate, national saving, and national investment are included as independent variables for this study; data were obtained from the Pakistan Bureau of Statistics and World Bank for the years (1980-2016). The results show that the relationship between Investment and Interest rate is negative, while the relationship between saving and interest rate is positive. There is a dire need to review the monetary policy issued by the State Bank of Pakistan.